2023
DOI: 10.1038/s41598-023-28768-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Cryptosporidium, Giardia, and Blastocystis from stray and household cats and cat owners in Tehran, Iran

Abstract: Cryptosporidiosis, giardiasis, and blastocystosis are among the most important parasitic diseases common between humans and cats. In addition, there are concerns about the possible transmission of zoonotic parasites from infected cats to humans. Hence, we investigated the molecular epidemiology of Cryptosporidium spp., Giardia duodenalis, and Blastocystis sp. in stray and household cats and cat owners. Our study was performed on 132, 33, and 33 fecal samples of stray and household cats, as well as cat owners i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…The information on G. duodenalis infection in cats is limited, and it has been reported only in certain regions of South Korea: with 3.8% in Jeju (Kwak and Seo, 2020) and 30.7% in Daejeon . The G. duodenalis infection rate in this study was higher than 2.3% in the United States (Bouzid et al, 2015), 7% in Denmark (Enemark et al, 2020), 1.4-3.6% in China , and 1.5% in Iran (Karimi et al, 2023). However, it was lower than Brazil at 9.0% (de Oliveira et al, 2021), Australia at 10.1% (Yang et al, 2015), and Turkey at 8.0% (Onder et al, 2021).…”
Section: Giardia Duodenalis Tpi Bg Gdh Mlgmentioning
confidence: 45%
See 1 more Smart Citation
“…The information on G. duodenalis infection in cats is limited, and it has been reported only in certain regions of South Korea: with 3.8% in Jeju (Kwak and Seo, 2020) and 30.7% in Daejeon . The G. duodenalis infection rate in this study was higher than 2.3% in the United States (Bouzid et al, 2015), 7% in Denmark (Enemark et al, 2020), 1.4-3.6% in China , and 1.5% in Iran (Karimi et al, 2023). However, it was lower than Brazil at 9.0% (de Oliveira et al, 2021), Australia at 10.1% (Yang et al, 2015), and Turkey at 8.0% (Onder et al, 2021).…”
Section: Giardia Duodenalis Tpi Bg Gdh Mlgmentioning
confidence: 45%
“…The housing environment of companion animals contributes to the prevalence of parasitic infection (Appelbee et al, 2005). Previous studies have reported a higher rate of C. felis infection in stray and shelter cats than in companion cats, although companions also show parasitic infection (Itoh et al, 2013;Li et al, 2021;Taghipour et al, 2021;Karimi et al, 2023). The present results showed that the detection of protozoa parasites varies depending on the habitat of cats and that the low rate of companion cat infection with Cryptosporidium and Cystoisospora is consistent with the breeding style of companion cats with less outside access in South Korea (Kim et al, 2018).…”
Section: Giardia Duodenalis Tpi Bg Gdh Mlgmentioning
confidence: 99%
“…According to Nemati et al [ 11 ], the first three, ST1, ST2, and ST3, are the most frequent STs among human subjects in the Asian continent. Karimi et al [ 97 ] indicated that approximately 90% of the Blastocystis STs isolated from human fecal samples worldwide belonged to ST1, ST2, ST3, and ST4. Some studies in developing countries reported the following Blastocystis spp.…”
Section: Discussionmentioning
confidence: 99%
“…These parasites are widespread and can infect humans, domestic animals, and wild animals. The cysts/oocysts of both parasites are shed in the feces of infected hosts and can be transmitted to new hosts via contaminated food, water, or direct contact with infected humans or animals [ 1 , 2 ]. Both protozoa have a monoxenous life cycle, a low infective dose, and a short prepatent period, which increase their potential for transmission in human and animal hosts [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both protozoa have a monoxenous life cycle, a low infective dose, and a short prepatent period, which increase their potential for transmission in human and animal hosts [ 3 ]. Some families keep domestic animals in their yards and share public places with them, increasing the potential for zoonotic transmission [ 2 ].…”
Section: Introductionmentioning
confidence: 99%